2021
DOI: 10.3390/ani11092480
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomics Analysis of Virulent Peptides Involved in Streptococcus suis Pathogenesis

Abstract: Streptococcus suis (S. suis) is a zoonotic pathogen causing severe streptococcal disease worldwide. S. suis infections in pigs and humans are frequently associated with the virulent S. suis serotype 2 (SS2). Though various virulence factors of S. suis have been proposed, most of them were not essentially accounted for in the experimental infections. In the present study, we compared the peptidomes of highly virulent SS2 and SS14 in humans, the swine causative serotypes SS7 and SS9, and the rarely reported sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 43 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Our study showed 100% identities of the genes in S. suis strains WUSS351, HN105, LS9N, YZDH1, FJSMS, and AH681 ( Table 1 ). ABC transporter ATP-binding protein/permease plays an important role in the transportation of various substrates, serves as an efflux pump, or is involve in biofilm formation ( Chaiden et al, 2021 ). Another study reported that the presence of ABC transporters in the virulent-to-humans SS2, SS14 strains, and non-virulent-to-humans SS7 strains indicated their possible involvement for the survival and then the pathogenesis of virulent S. suis in the host-simulated environment ( Chaiden et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed 100% identities of the genes in S. suis strains WUSS351, HN105, LS9N, YZDH1, FJSMS, and AH681 ( Table 1 ). ABC transporter ATP-binding protein/permease plays an important role in the transportation of various substrates, serves as an efflux pump, or is involve in biofilm formation ( Chaiden et al, 2021 ). Another study reported that the presence of ABC transporters in the virulent-to-humans SS2, SS14 strains, and non-virulent-to-humans SS7 strains indicated their possible involvement for the survival and then the pathogenesis of virulent S. suis in the host-simulated environment ( Chaiden et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…ABC transporter ATP-binding protein/permease plays an important role in the transportation of various substrates, serves as an efflux pump, or is involve in biofilm formation ( Chaiden et al, 2021 ). Another study reported that the presence of ABC transporters in the virulent-to-humans SS2, SS14 strains, and non-virulent-to-humans SS7 strains indicated their possible involvement for the survival and then the pathogenesis of virulent S. suis in the host-simulated environment ( Chaiden et al, 2021 ). We detected the ABC transporter ATP-binding protein/permease gene in several S. suis strains such as YSJ17, AKJ18, AH681, HN136, LS9N, and CZ130302 ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, RpsB (uS2) has been shown to be a surface-exposed protein of rickettsia, representing an important ligand and adhesin of these obligate intracellular microorganisms [ 87 ]. Increased expression of uS2-derived peptides has been observed in the highly virulent strains of Streptococcus suis cultured under host-simulated conditions, indicating that uS2 or its peptides might serve as specific virulence factors [ 88 ]. The role of uS2 in pathogenesis is obviously not related to its functions in the ribosome.…”
Section: Moonlighting R-proteins Of the 30s Ribosomal Subunitmentioning
confidence: 99%
“…As for the techniques capable of identifying the putative virulence factors, the proteome of S . suis has also been studied to consolidate their particular roles of putative virulence factors in the host as well [ 18 21 ]. Various putative virulence factors of SS2 have been proposed such as, acetaldehyde-CoA/alcohol dehydrogenase (adhE), catabolite control protein A (Ccp A), leucyl aminopeptidase (LAP), enolase (Eno), and endopeptidase [ 19 , 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous work, peptidomics analysis revealed the role of the ABC-type phosphate transport system (SSU05_1106) and 30S ribosomal protein S2 (rpsB) in the survival of S . suis in a growth medium supplemented with 5% sheep blood [ 18 ], since some bacteria or yeast are adaptive or responsive to different environments or growth conditions [ 25 28 ].…”
Section: Introductionmentioning
confidence: 99%